Toward a science of consciousness III : the third Tuscon discussions and debates - Hameroff, Stuart R; Kaszniak, Alfred W; Chalmers, David John (MIT Press, 1999)
Can there be a science of consciousness? This issue has been the focus of three landmark conferences sponsored by the University of Arizona in Tucson. The first two conferences and books have become touchstones for the field. This volume presents a selection of invited papers from the third conference. It showcases recent progress in this maturing field by researchers from philosophy, neuroscience, cognitive psychology, phenomenology, and physics. It is divided into nine sections: the explanatory gap, color, neural correlates of consciousness, vision, emotion, the evolution and function of consciousness, physical reality, the timing of conscious experience, and phenomenology. Each section is preceded by an overview and commentary by the editors. Contributors: Dick J. Bierman, Jeffrey Burgdorf, A. Graham Cairns-Smith, William H. Calvin, Christian de Quincey, Frank H. Durgin, Vittorio Gallese, Elizabeth L. Glisky, Melvyn A. Goodale, Richard L. Gregory, Scott Hagan, C. Larry Hardin, C. A. Heywood, Masayuki Hirafuji, Nicholas Humphrey, Harry T. Hunt, Piet Hut, Alfred W. Kaszniak, Robert W. Kentridge, Stanley A. Klein, Charles D. Laughlin, Joseph Levine, Lianggang Lou, Shimon Malin, A. David Milner, Steven Mithen, Martine Nida-Rumelin, Stephen Palmer, Jaak Panksepp, Dean Radin, Steven Z. Rapcsak, Sheryl L. Reminger, Antti Revonsuo, Gregg H. Rosenberg, Yves Rossetti, Jeffrey M. Schwartz, Jonathan Shear, Galen Strawson, Robert Van Gulick, Frances Vaughan, Franz X. Vollenweider, B. Alan Wallace, Douglas F. Watt, Larry Weiskrantz, Fred A. Wolf, Kunio Yasue, Arthur Zajonc.
Complex adaptive systems
Keywords: neurovědy; Consciousness; filozofie; emoce; psychologie, klinická psychologie; Philosophy; vědomí; Neurosciences; Emotions